2019
DOI: 10.31234/osf.io/xrp7y
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Detached Self: Investigating the Effect of Depersonalisation on Self-Bias in the Visual Remapping of Touch

Abstract: The sense of self lies at the heart of conscious experience, anchoring our disparate perceptions, emotions, thoughts and actions into a unitary whole. There is a growing consensus that sensory information about the body plays a central role in structuring this basic sense of self. Depersonalisation (DP) is an intriguing form of altered subjective experience in which people report feelings of unreality and detachment from their sense of self. Previous studies in healthy adults have showed a self-bias effect, na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Given the importance of self-face perception for one's sense of self and self-identity, we hypothesized that DP would influence self-prioritization of bodily self-associated stimuli (avatar faces) to a greater extent than abstract self-associated stimuli (geometrical shapes). This is in line with abovementioned work highlighting the strong relationship between atypical bodily self-awareness and DP experiences (Farmer et al, 2019;Sierra & David, 2011).…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Given the importance of self-face perception for one's sense of self and self-identity, we hypothesized that DP would influence self-prioritization of bodily self-associated stimuli (avatar faces) to a greater extent than abstract self-associated stimuli (geometrical shapes). This is in line with abovementioned work highlighting the strong relationship between atypical bodily self-awareness and DP experiences (Farmer et al, 2019;Sierra & David, 2011).…”
Section: Introductionsupporting
confidence: 92%
“…These findings extend to the research on self-face perception: one study found that people with depersonalization show increased neural activity when processing faces in the medial prefrontal cortex and the anterior cingulate cortex -areas responsible for processing of social and emotional information (Ketay et al, 2014). Finally, there is evidence of altered integration of tactile and visual representations of one's face in those experiencing high levels of depersonalization which may suggest that changes in multisensory perception of the self may underlie the phenomenology of depersonalization (Farmer et al, 2019).…”
Section: Discussionmentioning
confidence: 73%
“…The multimodal integration of exteroceptive signals such as the tactile and visual stimuli employed in the rubber hand illusion and in Adler et al's study are thought to occur in several temporal and parietal lobe areas (Calvert and Thesen, 2004), especially the insula (Bushara et al, 2001;Bushara et al, 2003), and disruptions in this process have been proposed as a possible explanation for feelings of disembodiment in DPD (Farmer et al, 2019;O'Sullivan et al, 2018). Indeed, participants with frequent symptoms of depersonalisation (high CDS scores) appear to be more susceptible to feelings of illusory ownership of a rubber hand than those with infrequent symptoms (Kanayama et al 2009).…”
Section: Have Been Instrumentalmentioning
confidence: 86%
“…Furthermore, if the limbic contributions are part of what it is for self-related contents to be salient, then limbic contributions are part of self-bias processing. 22 Indeed, depersonalized patients do not benefit from self-bias (Farmer et al 2020).…”
Section: )mentioning
confidence: 99%